P031 Effects of tobacco alkaloids on DSS-induced colitis mouse model. (16th January 2018) - Lo Sasso, G; Phillips, B; Gadaleta, R; Elamin, A; Kondylis, A; Ivanov, N; Hoeng, J
Abstract: Background: IBD is the collective term for chronic immune-mediated diseases of unknown, multifactorial aetiology with complex interactions between genetic and environmental factors, comprising two main disease manifestations, Ulcerative colitis (UC) and Crohn's disease (CD). Decades of epidemiological and clinical based evidence from robust case controlled studies clearly point to an inverse association between smoking and the onset and development of ulcerative colitis (UC). Contrarily, cigarette smoke is associated with a higher incidence risk and increased severity of Crohn's disease progression. However, the biological mechanisms responsible of the underlined smoking effects on UC progression remain largely elusive. Several studies have demonstrated the anti-inflammatory action of cholinergic agonists, such as the main tobacco alkaloid nicotine. The contrasting results observed in clinical studies addressing the role of nicotine in UC opened new questions on the molecular mechanisms at the base of the intrinsic nicotinic anti-inflammatory activity and the possible involvement of other tobacco alkaloids in the observed reduced ulcerative colitis disease risk, progression and relapse rate in smokers. In the present study we aimed to investigate the potential preventive anti-inflammatory activity of a tobacco alkaloid (Alkaloid #1), structurally similar to nicotine, in a murine model of intestinal inflammation. Methods: UC-like symptoms were induced in C57BL/6 male mice ( n = 14) by 3.5% DSS administration for 7 days. Mice were then treated with nicotine and Alkaloid #1 at 2 different concentrations in drinking water for a total of 21 days (14 days pre-DSS + 7 days during DSS). During the treatment animals were evaluated for progression and severity of UC symptoms. Results: Daily observations (body weight, intestinal bleeding, hematochezia, etc.) and cytokine analysis revealed a protective alkaloid-related effect. Although no differences observed on the histological analysis of colons, alkaloid-treated mice showed a reduced body weight loss, intestinal bleeding and hematochezia. Further molecular analysis are ongoing to investigate the molecular mechanisms implicated in the disease progression and amelioration. Conclusions: Further molecular analysis are ongoing to investigate the molecular mechanisms implicated in the disease progression and amelioration.